Analysis of the Utilization of Campus Green Open Space at Narotama University Surabaya - Ahmad Ariq Rabbani; Julistyana Tistogondo; Ronny Durrotun Nasihien (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2021)
Environmental problems have become one of the things that are most often considered in recent years, the problems that we often hear about are the problems of globalization. The problem of globalization has led to many innovations among the community, especially in universities, namely the Green Campus. Green Open Space (RTH) has become a key indicator in Green Campus-based spatial planning. Along with the increasing number of physical infrastructure developments, the existence of private Green Open Space (GOS) has also begun to decrease and change functions. This study aims to determine the extent of Green Open Space (GOS) in the Narotama University Surabaya. The total value of the Green Area Coefficient (GAC) of Narotama University Surabaya is 10.7%, which value has fulfilled the minimum requirement for private green open space, which is 10%. Narotama University Surabaya is also not ready to become a green campus, due to the existence of a smoking area, where criteria for a green campus are that there should be no smoking area within the campus.